Pengaruh Konsentrasi Larutan Getah Tangkai Daun Kamboja Putih (Plumeria Acuminata. W.T.Ait)Terhadap Pertumbuhan Bakteri Streptococcus Mutans (In vitro ) - Damayanti, Vivi Novia; , drg.Mahmud Kholifa, MDSc; , drg.Fitria Nur Malita Sari (2016)
Dental caries is an infectious disease which damages the structures of teeth ranging from email, dentin and pulpayang caused by several factors, namely the host, substrate, time, and microorganisms one that causes dental caries is Streptococcus mutans. Dental caries can be prevented mechanically and chemically. Chemical means to do with the use of mouthwash, but the use of mouthwash can have side effects such as changing the color of teeth so that the required new innovation with natural ingredients that are safer and more affordable. One of these natural ingredients is the sap of the leaf stalk white frangipani which contains flavonoids, alkaloids, tannins and triterpenoids as an antibacterial. This research aims to determine the effect of solution concentration petiole sap white frangipani against Streptococcus mutans bacteria growth inhibition and determine the optimal concentration in inhibiting the growth of bacteria streptococcus mutans Method used is by measuring the diameter of the clear zone around the wells were formed after the petri dish of bacteria Streptococcus mutans treated petiole sap concentration of white frangipani concentration of 10%, 20%, 40%, 80% and 0.2% chlorhexidine. The statistical test result with Anova test showed p = 0.00 (p <0.05). The results indicate that there are significant concentrations of petiole sap white frangipani against Streptococcus mutans bacteria growth inhibition. Post hoc test showed p = 0.00 (p <0.05), which means that any increase in the concentration of petiole sap white frangipani followed by the increase in average diameter zone of inhibition of bacterial growth Streptococcus mutans significantly.